AUDIOVISUAL TRANSLATION: THE CHALLENGE OF DUBBING A WORLD CLASSIC - Mallo Lapuerta, Ana Mª (Entreculturas. Revista de traducción y comunicación intercultural, 2016)
The universal stage classic Cyrano de Bergerac (Paris, 1897) consists of 2 570 lines written in alexandrine couplets where the rhyme scheme alternates a combination of French Classic and Romantic theatre. From the standpoint of audiovisual translation, the difficulties involved in preserving the idiosyncratic features of verse and rhyme in the original play and in the film by Rappenau become extremely interesting aspects of the whole linguistic transfer. The language-based analysis of the complete audiovisual work , following the several translation procedures involved and bearing in mind discursive and pragmatic modifications involved in the French>Spanish translation for dubbing purposes points at a number of interesting observations in the domain of translation itself.